Hubungan Antara Trust dengan Konflik Interpersonal Pada Dewasa Awal yang Menjalani Hubungan Pacaran Jarak Jauh - Winayanti, Ratna Devy; Widiasavitri, Putu Nugrahaeni (Jurnal Psikologi Udayana, 2016)
Long-distance relationship has now become a social trend among the community because of the increase in educational attainment of men and women. Trust is a prerequisite of success in a long-distance relationship, and it is important to minimize conflict. This study aims to determine the correlation between trust and interpersonal conflict among early adulthood initial long-distance relationship. Subjects in this study were 100 student of Udayana University. Measuring instruments used are the trust scale (34 items; rxx` = 0.913) and interpersonal conflict scale (33 items; rxx` = 0.878). Data were processed using Pearson Product Moment analysis and simple linear regression. Statistical analysis show, there is significant correlation between trust and interpersonal conflict, with a negative direction (r = -0.325 ; p = 0.001). The coefficient of determination obtained for 0.106 which means that 10.6% of trust variable can explaine variance that occurs in conflict interpersonal variable. Keywords: trust, interpersonal conflict, long-distance relationship, early adulthood